Mobility of coated and uncoated TiO2 nanomaterials in soil columns – Applicability of the tests methods of OECD TG 312 and 106 for nanomaterials. (1st July 2015) - Nickel, Carmen; Gabsch, Stephan; Hellack, Bryan; Nogowski, Andre; Babick, Frank; Stintz, Michael; Kuhlbusch, Thomas A.J.
Abstract: Nanomaterials are commonly used in everyday life products and during their life cycle they can be released into the environment. Soils and sediments are estimated as significant sinks for those nanomaterials. To investigate and assess the behaviour of nanomaterials in soils and sediments standardized test methods are needed. In this study the applicability of two existing international standardized test guidelines for the testing of nanomaterials, OECD TG 106 "Adsorption/Desorption using a Bath Equilibrium Method" and the OECD TG 312 "Leaching in Soil Columns", were investigated. For the study one coated and two uncoated TiO2 nanomaterials were used, respectively. The results indicate that the OECD TG 106 is not applicable for nanomaterials. However, the test method according to OECD TG 312 was found to be applicable if nano-specific adaptations are applied. The mobility investigations of the OECD TG 312 indicated a material-dependent mobility of the nanomaterials, which in some cases may lead to an accumulation in the upper soil layers. Whereas no significant transport was observed for the uncoated materials for the double-coated material (coating with dimethicone and aluminiumoxide) a significant transport was detected and attributed to the coating. Highlights: A low mobility of all nanomaterials and no breakthrough was observed. The coated nanomaterial shows the highest mobility. The low mobility may lead to an accumulation of nanomaterials in the upper soil. The OECD TG 312 was found to be applicable for nanomaterials. The OECD TG 106 was found to be not applicable for nanomaterials.